Penerapan Metode Simple Additive Weighting pada Sistem Pendukung Keputusan untuk Menentukan Hari Banyaknya Pembeli (Studi Kasus Toko Baju Spring) - Zainudin; Dede Supian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to develop a decision support system (DSS) to determine the busiest shopping days at Toko Baju Spring using the Simple Additive Weighting (SAW) method. The background of this research is the difficulty faced by store owners in predicting busy days due to the many criteria and supplier alternatives considered. The manual selection process, which is still subjective and based on estimates, often leads to errors in decision-making, affecting stock availability, customer satisfaction, and store profitability. The SAW method is applied to provide a more systematic, objective, and accurate approach in ranking days based on predetermined criteria. The research stages include data collection through observation, literature study, and interviews, followed by system design and implementation using web programming (PHP) and MySQL database. The results show that the SAW-based DSS can effectively assist store owners in identifying the busiest days, thereby optimizing stock preparation and minimizing the risk of loss. This study contributes to the practical application of multi-criteria decision-making methods in small retail business management and provides a reference for similar implementations